Aluminum-catalyzed statistical copolymerization of mono-, tri- and penta-fluorophenyl glycidyl ether with ethylene oxide and epichlorohydrin. Issue 38 (14th September 2021) - Guo, Fang; Deng, Ming; Li, Fan; Chen, Shoulong
Abstract : A novel family of fluorine-polyethers with a high molecular weight and controlled fluorine distribution was prepared by the copolymerization of fluorophenyl glycidyl ether with ethylene oxide and epichlorohydrin catalyzed by i -Bu3 Al/H3 PO4 /DBU. Abstract : The copolymerization of fluorophenyl glycidyl ether (FPGE, including 4-monofluorophenyl glycidyl ether (MFPGE), 3, 4, 5-trifluorophenyl glycidyl ether (TFPGE) and 2, 3, 4, 5, 6-pentafluorophenyl glycidyl ether (PFPGE)) with ethylene oxide (EO) and epichlorohydrin (ECH) by an aluminium-based catalyst i -Bu3 Al/H3 PO4 /DBU afforded a new series of fluorine-polyethers with a high molecular weight and controlled fluorine distribution. Fluorine could be random, gradient, tapered and block incorporated into poly(EO) and poly(ECH) quantitatively. The simultaneous copolymerization of FPGE with EO afforded MFPGE–EO, TFPGE–EO and PFPGE–EO copolymers with random, gradient, and tapered distribution of fluorine, respectively. The simultaneous copolymerization of FPGE with ECH afforded MFPGE–ECH, TFPGE–ECH and PFPGE–ECH copolymers with random and gradient distribution of fluorine, respectively. The sequential copolymerization of FPGE with EO and ECH afforded diblock and triblock copolymers such as EO–FPGE, ECH–FPGE, EO–FPGE–EO, and ECH–FPGE–ECH with block distribution of fluorine. The fluorine distribution of the obtained polyethers had a significant effect on their mechanical properties.